NK Cell-Based Immunotherapy and Therapeutic Perspective in Gliomas - Pan, Changqing; Zhai, You; Li, Guanzhang; Jiang, Tao; Zhang, Wei (Frontiers in Oncology, 2021)
Glioma is the most common malignant primary brain tumor diagnosed in adults. Current therapies are unable to improve its clinical prognosis, imposing the need for innovative therapeutic approaches. The main reason for the poor prognosis is the great cell heterogeneity of the tumor and its immunosuppressive microenvironment. Development of new therapies that avoid this immune evasion could improve the response to the current treatments. Natural killer (NK) cells are an intriguing candidate for the next wave of therapies because of several unique features that they possess. For example, NK cell-based immunotherapy causes minimal graft-versus-host disease. Cytokine release syndrome is less likely to occur during chimeric antigen receptor (CAR)-NK therapy, and CAR-NK cells can kill targets in a CAR-independent manner. However, NK cell-based therapy in treating glioma faces several difficulties. For example, CAR molecules are not sufficiently well designed so that they will thoroughly release functioning NK cells. Compared to hematological malignancies, the application of many potential NK cell-based therapies in glioma lags far behind. Here, we review several issues of NK cells and propose several strategies that will improve the efficacy of NK cell-based cancer immunotherapy in the treatment of glioma.